When Tokyo Ruled the Hill - Johnson, Kim (Express)
Tokyo Steel Orchestra gave a great performance but their elimination from the Panorama semi-finals must have deeply hurt them and all the people of John John. While neither of the two great community bands, Desperadoes and Tokyo, were very good in the earlies, the hill boys climbed out of that by the sixties.
Keywords: Steel bands (Music) -- Trinidad and Tobago -- History; Steel band music -- Trinidad and Tobago; Steel bands (Music) -- Competitions -- Trinidad and Tobago